Using Language Portraits to Promote Critical Self-Reflection for Teaching Multilingual Students - Tigert, Johanna M.; Crawford, Jessica; Jones, Loren; Fotouhi, Golnar; Peercy, Megan Madigan; Hardy-Skeberdis, Melanie; Fredricks, Daisy E. (Routledge, Taylor & Francis Group, 2026)
The study examined how pre-service teachers (PSTs) of Teaching English for Speakers of Other Languages used language portraits to express their identities visually and in writing. We conducted a qualitative analysis of both the visual and ideological layers of the portraits, focusing on what identity elements PSTs included or did not include in them, and the level of criticality achieved in their multimodal reflection. We found most color choices PSTs made were arbitrary, but certain languages were linked to body parts through function or emotion. Patterns indicating language hegemonies and legitimacy emerged through language inclusion and omission, and only few PSTs depicted translanguaging on their portraits. Lastly, engagement with race varied, with white PSTs often avoiding racial representation. Our findings highlight the need for teacher educators to foster deeper discussions on race and language ideologies and use the portrait assignment to promote more critical reflection. Discussing language portraits would help PSTs challenge internalized assumptions and develop more humanizing understandings of themselves and their pedagogies.